The Importance of Being “That” Colorectal pT1: A Combined Clinico-Pathological Predictive Score to Improve Nodal Risk Stratification - Gambella, Alessandro; Falco, Enrico Costantino; Benazzo, Giacomo; Osella-Abate, Simona; Senetta, Rebecca; Castellano, Isabella; Bertero, Luca; Cassoni, Paola (Frontiers in Medicine, 2022)
The management of endoscopically resected pT1 colorectal cancer (CRC) relies on nodal metastasis risk estimation based on the assessment of specific histopathological features. Avoiding the overtreatment of metastasis-free patients represents a crucial unmet clinical need. By analyzing a consecutive series of 207 pT1 CRCs treated with colectomy and lymphadenectomy, this study aimed to develop a novel clinicopathological score to improve pT1 CRC metastasis prediction. First, we established the clinicopathological profile of metastatic cases: lymphovascular invasion (OR:23.8; CI:5.12-110.9) and high-grade tumor budding (OR:5.21; CI:1.60-16.8) correlated with an increased risk of nodal metastasis, while age at diagnosis >65 years (OR:0.26; CI:0.09-0.71) and high tumor-infiltrating lymphocytes (OR:0.19; CI:0.06-0.59) showed a protective effect. Combining these features, we built a five-tier risk score that, applied to our series, identified cases with a higher risk (score ≥ 2) of nodal metastasis (OR:7.7; CI:2.4-24.4). Notably, a score 0 was only assigned to cases with no metastases (13/13 cases) and all the score 4 samples (2/2 cases) showed nodal metastases. In conclusion, we developed an effective combined score to assess pT1 CRC nodal metastasis risk. We believe that its adoption within a multidisciplinary pT1 unit could improve patients’ clinical management and limit surgical overtreatment.